ISLAMIC RELIGIOUS EDUCATION AS A FOUNDATION FOR PROFESSIONAL ETHICS IN THE ENFORCEMENT OF ISLAMIC LAW - Muhammad Faisal Azmi (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The increasing complexity of contemporary legal practices has raised concerns regarding the ethical integrity and professionalism of law enforcement within Islamic legal systems. In many cases, the weakening of moral values among legal practitioners has affected the implementation of justice and public trust. This article aims to examine the role of Islamic Religious Education as a foundational framework for shaping professional ethics in the enforcement of Islamic law. The study employs a qualitative library research method by analyzing relevant literature, scholarly articles, and classical as well as contemporary Islamic educational perspectives. The findings indicate that Islamic Religious Education contributes significantly to the development of ethical awareness, moral responsibility, honesty, justice, and accountability among law enforcement professionals. Furthermore, the integration of Islamic ethical values into educational processes strengthens professional conduct and supports the realization of fair and humane Islamic law enforcement. This study concludes that Islamic Religious Education serves not only as a spiritual foundation but also as an ethical instrument for enhancing professionalism and integrity in Islamic legal practices.